2020
DOI: 10.1002/hon.2805
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic models integrating quantitative parameters from baseline and interim positron emission computed tomography in patients with diffuse large B‐cell lymphoma: post‐hoc analysis from the SAKK38/07 clinical trial

Abstract: Positron emission computed tomography (PET/CT) in patients with diffuse large B-cell lymphoma (DLBCL) enrolled in a prospective clinical trial were reviewed to test the impact of quantitative parameters from interim PET/CT scans on overall (OS) and progression-free (PFS) survival. We centrally reviewed baseline and interim PET/CT scans of 138 patients treated with rituximab plus cyclophosphamide, doxorubicin, vincristine and prednisone given every 14 days (R-CHOP14) in the SAKK38/07 trial (ClinicalTrial.gov id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
(140 reference statements)
0
11
1
Order By: Relevance
“…Patients in the high-risk subgroup had more frequently elevated LDH and high IPI scores than the other groups. This is not surprising as LDH is a surrogate marker of disease burden: we might speculate that increased LDH levels reflect the elevated MTV, which this analysis confirmed to be an optimal individual parameter to identify patients at high risk of progression or death [ 17 , 22 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Patients in the high-risk subgroup had more frequently elevated LDH and high IPI scores than the other groups. This is not surprising as LDH is a surrogate marker of disease burden: we might speculate that increased LDH levels reflect the elevated MTV, which this analysis confirmed to be an optimal individual parameter to identify patients at high risk of progression or death [ 17 , 22 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 76%
“…The metabolic response in 18F-fluorodeoxyglucose (18FDG) positron emission tomography/computed tomography (PET/CT) scan at the end of treatment is currently the best predictor of patient survival [ 18 ]. Increasing evidence suggests that baseline PET/CT parameters, including metabolic tumor volume (MTV), total lesion glycolysis (TLG) [ 19 , 20 , 21 , 22 , 23 ], and metabolic heterogeneity (MH) and radiomic features indicating lymphoma dissemination, represent independent and powerful prognostic factors in DLBCL [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Response to interim F 18 flurodeoxyglucose positron emission tomography/computed tomography (PETCT) during frontline chemoimmunotherapy has been explored as a prognostic marker in newly diagnosed DLBCL in multiple studies with small sample size, heterogeneous timing of interim PETCT, heterogeneous populations, variable study treatments and conflicting results [ 5 12 ]. Three major prospective studies have evaluated impact of PETCT after cycles 2 of frontline chemoimmunotherapy (PET2) on outcomes of newly diagnosed DLBCL with conflicting results [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…DLBCL patients are traditionally evaluated after 2–4 regimens, and residual disease after treatment also indicates prognosis. Several studies found that interim evaluation results from PET-CT or CT scans are predictors of survival ( 13 15 ), but given the considerable portion of false-positive PET-CT scans, interim evaluation is not strictly associated with survival.…”
Section: Introductionmentioning
confidence: 99%